Assessing the Effects of Remote Working in the OR Tambo District Municipality - YAMKELA NTANDO; MAXHOBANDILE NDAMASE (African Journal of Governance and Development, 2024)
The COVID-19 pandemic necessitated a global shift to remote work, significantly altering public sector operations. This transition required the public sector to adapt from traditional manual working methods to a new normal of working from home. The shift to remote working posed significant challenges, particularly in service delivery within the public sector. Understanding these challenges and the overall impact of remote work is crucial for improving future operations. Investigating the transition in the OR Tambo District Municipality provides insights into the broader implications of remote working in the public sector. It helps to identify both the obstacles and benefits experienced during this shift. This study employed a qualitative research design, using unstructured interviews with fifteen respondents selected through purposive sampling. Data was analysed using a thematic approach to uncover patterns and themes related to the transition. The study revealed that the transition to remote working in the public sector faced significant hurdles, particularly affecting service delivery. Despite these challenges, remote working was found to be effective and efficient in certain areas, such as expediting administrative tasks within the OR Tambo district municipality where this study was conducted. The study concludes that remote working has both advantages and disadvantages in the public sector. It recommends addressing the challenges to smooth service delivery and administration while leveraging the efficiencies gained from remote working. This could involve investing in technology, training, and support systems to enhance the effectiveness of remote work in the public sector.